PREDICTION OF LIVE BODY WEIGHT USING BODY MEASUREMENTS FOR JAWA BREBES (JABRES) CATTLE - M. S. Haq; I G. S. Budisatria; P. Panjono; D. Maharani (Journal of Animal and Plant Sciences, 2020)
Bodyweight estimation is important for any aspect of livestock management. Jabres cattle farmers use bodyweight estimation to determine the cattle price in the traditional market. Nowadays, they only use eye-based assessment to predict cattle body weight with a lot of inaccuracies. In this study, the cattle body weight was estimated based on body size measurements data, namely body length, heart girth, withers height, rump height, face length, and face width. The data were collected from Jabres cattle reared in the district of Bantarkawung, Brebes, Central Java, Indonesia. The data were taken from 521 Jabres cattle which were stratified by sex and age. Generally, male Jabres cattle have a smaller body size than female Jabres cattle and younger cattle have significant smaller body size than elder cattle. The highest correlation coefficient came from body weight and heart girth. The equation to predict body weight was obtained by multiple linear regression and factorial analysis scores followed by multiple linear regression methods. The result showed that multiple linear regression method was preferable to be used to predict body weight of Jabres cattle because of its better accuracy, better fitness, and more applicable for Jabres cattle farmers.
Keywords: Body weight prediction; Jabres cattle; native cattle; Indonesia